2023
DOI: 10.1103/physrevlett.131.068301
|View full text |Cite
|
Sign up to set email alerts
|

Large Scale Zigzag Pattern Emerging from Circulating Active Shakers

Abstract: We report the emergence of large zig-zag bands in a population of reversibly actuated magnetic rotors that behave as active shakers, namely squirmers that shake the fluid around them without moving. The shakers collectively organize into dynamic structures displaying self-similar growth, and generate topological defects in form of cusps that connect vortices of rolling particles with alternating chirality. By combining experimental analysis with particle-based simulation, we show that the special flow field cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 69 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…Such a setting can arise either in a flocking mode, 54 in which case particles can rotate but are more likely to rotate together, or when the particles are all oriented due to an external field. 55 In the latter case, the point particles we consider do not experience a torque, but particles with a finite size will experience a torque. From Faxén's second law 56 in 2D we expect T ∝ a 2 (∇ × v ).…”
Section: Discussionmentioning
confidence: 99%
“…Such a setting can arise either in a flocking mode, 54 in which case particles can rotate but are more likely to rotate together, or when the particles are all oriented due to an external field. 55 In the latter case, the point particles we consider do not experience a torque, but particles with a finite size will experience a torque. From Faxén's second law 56 in 2D we expect T ∝ a 2 (∇ × v ).…”
Section: Discussionmentioning
confidence: 99%
“…The red dots represent the magnetic particles, which flow along the zigzag-shaped bands. Credit: G. Junot et al [1] oscillation caused each particle to roll like a pencil on a table in alternate directions about four times per second while keeping its long axis aligned with the others.…”
Section: Vide Omentioning
confidence: 99%
“…hen molecules or bacteria organize into a long-range pattern, researchers want to understand how the microscopic interactions lead to the macroscopic order. Pietro Tierno of the University of Barcelona and his colleagues observed such self-organization in magnetic particles suspended in a liquid and subjected to an oscillating magnetic field [1]. Through experiments and simulations, the team showed that the resulting zigzag pattern is explained by the fluid flow generated around the oscillating particles, not by any details of the particles or the applied field.…”
mentioning
confidence: 99%
See 1 more Smart Citation